Face Perception Is Modulated by Sexual Preference - Kranz, Felicitas; Ishai, Alumit (Current biology, 2006)
Face perception is mediated by a distributed neural system in the human brain [1, 2]. The response to faces is modulated by cognitive factors such as attention, visual imagery, and emotion [3–6]; however, the effects of gender and sexual orientation are currently unknown. We used fMRI to test whether subjects would respond more to their sexually preferred faces and predicted such modulation in the reward circuitry. Forty heterosexual and homosexual men and women viewed photographs of male and female faces and assessed facial attractiveness. Regardless of their gender and sexual orientation, all subjects similarly rated the attractiveness of both male and female faces. Within multiple, bilateral face-selective regions in the visual cortex, limbic system, and prefrontal cortex, similar patterns of activation were found in all subjects in response to both male and female faces. Consistent with our hypothesis, we found a significant interaction between stimulus gender and the sexual preference of the subject in the thalamus and medial orbitofrontal cortex, where heterosexual men and homosexual women responded more to female faces and heterosexual women and homosexual men responded more to male faces. Our findings suggest that sexual preference modulates face-evoked activation in the reward circuitry.